A novel salt-resistant polymer oil-displacing agent and preparation method thereof
By stirring and mixing quaternized polysulfone, epoxy nanosilica, coal asphalt resin and 2-acrylamide-2-methylpropanesulfonic acid to form a crosslinked structure, the problem of insufficient salt resistance performance of the existing oil repellent under high temperature and high mineralization conditions is solved, and a better oil repellent effect is achieved.
Patent Information
- Application Number
- CN202410042221.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-11
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-01-11
AI Technical Summary
The oil repellent in the three oil productions is difficult to maintain good viscosity-enhancing ability and salt resistance under high temperature and high mineralization conditions, which affects the recovery rate.
Using a new method of preparing a salt-resistant polymer oil flooding agent, a crosslinked structure is formed to enhance the temperature and salt resistance of the polymer by stirring and mixing quaternized polysulfone, epoxy nanosilica, coal asphalt resin and 2-acrylamide-2-methylpropanesulfonic acid.
The new salt-resistant polymer oil flooding agent exhibits good temperature and salt resistance under high temperature and high salt conditions, enhancing its oil flooding effect in the reservoir.
Smart Images

Figure BDA0004659858390000081 
Figure BDA0004659858390000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil displacement agents, in particular to a novel salt-resistant polymer oil displacement agent and a preparation method thereof. Background Art
[0002] At present, the reservoir temperature and mineralization in tertiary oil recovery are high. In order for the oil displacement agent to achieve the ideal effect, the polymer must have good viscosity increasing ability and temperature and salt resistance. Oil is a non-renewable resource. The exploitation and reserves of oil are closely related to the national economy. Continuously improving the recovery rate is the key to oil field development.
[0003] Coal tar-based water-absorbing resin can be prepared using the liquid oxide after alkali oxidation of coal tar as raw material. The selection of non-ionic hydrophilic groups can improve the salt resistance of the water-absorbing resin. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies of the prior art, the present invention provides a novel salt-resistant polymer oil-displacing agent and a preparation method thereof, which has a good salt-resistant effect.
[0006] (II) Technical solution
[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a novel salt-resistant polymer oil-displacing agent, the method for preparing the novel salt-resistant polymer oil-displacing agent comprising the following steps:
[0008] (1) 30-50 parts by weight of coal tar pitch is crushed, passed through a 180-200 mesh sieve, and 20-40 parts by weight of powder is obtained, which is dried at 60-80° C. to constant weight, and then a mixed solution of 10-15 parts by weight of potassium hydroxide and 20-30 parts by weight of deionized water is added thereto, and 3-4 MPa of oxygen is introduced. After 1 hour, the temperature is raised to 220-250° C., and the oxidation is carried out at a constant temperature for 2-3 hours. After the oxidation is completed, the powder is filtered to obtain alkalized coal tar pitch;
[0009] (2) adding alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol to deionized water to obtain solution A, adding a mixed solution B of sodium persulfate solution and N,N'-methylenebisacrylamide solution after stirring, stirring evenly, reacting in a water bath at 70-90° C. for 10-20 minutes, filtering and drying to obtain coal tar resin;
[0010] (3) adding quaternized phenol, 4,4-dichlorodiphenyl sulfone, and bisphenol A to N-methylpyrrolidone, stirring evenly, and then continuing to add potassium carbonate, first raising the temperature to 150-170° C. for azeotropic dehydration for 2-4 hours, and then raising the temperature to 100-180° C. for reaction for 6-10 hours, cooling, centrifuging, washing with water and ethanol in sequence, and drying to obtain quaternized polysulfone;
[0011] (4) Add quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid into a stirrer and stir for 2-4 hours to obtain a new salt-resistant polymer oil displacement agent.
[0012] Preferably, the mass ratio of alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone and polyethylene glycol in the (2) solution A is 1.2-1.5:1:2.1-2.3:2.2-2.4:0.8-1.4.
[0013] Preferably, the mass ratio of the sodium persulfate solution to the N,N'-methylenebisacrylamide solution in the (2) mixed solution B is 0.8-1.2:1.1-1.3.
[0014] Preferably, the mass ratio of solution A to mixed solution B in (2) is 1.2-1.5:1.
[0015] Preferably, the mass ratio of quaternized phenol, 4,4-dichlorodiphenyl sulfone, bisphenol A and potassium carbonate in (3) is 1.2-1.5:1:0.9-1.5:0.1-0.2.
[0016] Preferably, the preparation method of the quaternized phenol in (3) is: adding 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent for dissolution, then adding p-hydroxyphenylethanol for reaction, heating in a water bath at 70-90° C. for reaction for 6-10 hours, washing with anhydrous ethanol after the reaction, and drying to obtain the quaternized phenol.
[0017] Preferably, the mass ratio of the 2,3-epoxypropyltrimethylammonium chloride to p-hydroxyphenylethanol is 1.1-1.3:1.
[0018] Preferably, the mass ratio of quaternized polysulfone, epoxy nano-silica, coal tar resin and 2-acrylamide-2-methylpropane sulfonic acid in (4) is 2.1-2.5:1:2.3-2.6:1.5-1.8.
[0019] Preferably, it is obtained by the preparation method according to any one of claims 1 to 8.
[0020] (III) Beneficial technical effects
[0021] The invention prepares a novel salt-resistant polymer oil-displacing agent by adding quaternized polysulfone, epoxy nano-silicon dioxide, coal tar resin and 2-acrylamide-2-methylpropane sulfonic acid into a stirrer and stirring.
[0022] During the stirring and mixing process, epoxy nano-silica will undergo a ring-opening reaction with the hydroxyl groups in the quaternary ammonium polysulfone and the amino groups in the coal tar resin, and cross-linking will occur between the three. Due to the existence of the cross-linking structure, the rigidity of the polymer in the new salt-resistant polymer oil displacement agent is enhanced, and the benzene ring structure contained in the polymer further enhances its rigidity and increases the difficulty of conformation, so it has better temperature and salt resistance. Quaternary ammonium polysulfone and coal tar resin themselves have good salt resistance.
[0023] The new salt-resistant polymer oil-displacing agent has a larger side group, which increases the steric hindrance and resistance to hydrolysis. The sulfonic acid group, quaternary ammonium salt, hydroxyl group and amino group can improve the salt resistance and form hydrogen bonds with each other, reducing the degree of freedom of the component polymer chains, increasing the macromolecular fluid mechanics volume, forming a dynamic network structure, and improving the salt resistance of the polymer oil-displacing agent. DETAILED DESCRIPTION
[0024] Example 1
[0025] (1) 30 parts by weight of coal tar pitch were crushed, passed through a 180-mesh sieve, and 20 parts by weight of powder were obtained, which was then dried at 60° C. to constant weight, and then a mixed solution of 10 parts by weight of potassium hydroxide and 20 parts by weight of deionized water was added thereto, and 3 MPa of oxygen was introduced. After 1 hour, the temperature was raised to 220° C. and oxidized at a constant temperature for 2 hours. After the oxidation was completed, the powder was filtered to obtain alkalized coal tar pitch;
[0026] (2) adding alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol to deionized water to obtain solution A, wherein the mass ratio of alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol is 1.2:1:2.1:2.2:0.8, stirring, adding a mixed solution B of sodium persulfate solution and N,N'-methylenebisacrylamide solution, wherein the mass ratio of sodium persulfate solution and N,N'-methylenebisacrylamide solution is 0.8:1.1, and the mass ratio of solution A to mixed solution B is 1.2:1, stirring evenly, reacting in a water bath at 70°C for 10 minutes, filtering and drying to obtain coal tar resin;
[0027] (3) adding 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent to dissolve it, and then adding p-hydroxyphenylethanol to react, wherein the mass ratio of 2,3-epoxypropyltrimethylammonium chloride to p-hydroxyphenylethanol is 1.1:1, heating in a water bath at 70° C., reacting for 6 hours, washing with anhydrous ethanol after the reaction, and drying to obtain quaternized phenol;
[0028] (4) adding quaternized phenol, 4,4-dichlorodiphenyl sulfone, and bisphenol A to N-methylpyrrolidone, stirring evenly, and then continuing to add potassium carbonate, wherein the mass ratio of quaternized phenol, 4,4-dichlorodiphenyl sulfone, bisphenol A, and potassium carbonate is 1.2:1:0.9:0.1, first raising the temperature to 150° C. for azeotropic dehydration for 2 hours, then raising the temperature to 100° C. for reaction for 6 hours, cooling, centrifuging, washing with water and ethanol in sequence, and drying to obtain quaternized polysulfone;
[0029] (5) Add quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid into a stirrer, wherein the mass ratio of quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid is 2.1:1:2.3:1.5, and stir for 2 hours to obtain a new salt-resistant polymer oil displacement agent.
[0030] Example 2
[0031] (1) 50 parts by weight of coal tar pitch was crushed and passed through a 200-mesh sieve to obtain 40 parts by weight of powder, which was then dried at 80° C. to constant weight, and then a mixed solution of 15 parts by weight of potassium hydroxide and 30 parts by weight of deionized water was added thereto, and 4 MPa of oxygen was introduced. After 1 hour, the temperature was raised to 250° C. and oxidized at a constant temperature for 3 hours. After the oxidation was completed, the powder was filtered to obtain alkalized coal tar pitch;
[0032] (2) adding alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol to deionized water to obtain solution A, wherein the mass ratio of alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol is 1.5:1:2.3:2.4:1.4, stirring, adding a mixed solution B of sodium persulfate solution and N,N'-methylenebisacrylamide solution, wherein the mass ratio of sodium persulfate solution and N,N'-methylenebisacrylamide solution is 1.2:1.3, and the mass ratio of solution A to mixed solution B is 1.5:1, stirring evenly, reacting in a water bath at 90°C for 20 minutes, filtering and drying to obtain coal tar resin;
[0033] (3) adding 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent to dissolve it, and then adding p-hydroxyphenylethanol to react, wherein the mass ratio of 2,3-epoxypropyltrimethylammonium chloride to p-hydroxyphenylethanol is 1.3:1, heating in a water bath at 90° C., reacting for 10 hours, washing with anhydrous ethanol after the reaction, and drying to obtain quaternized phenol;
[0034] (4) adding quaternized phenol, 4,4-dichlorodiphenyl sulfone, and bisphenol A to N-methylpyrrolidone, stirring evenly, and then continuing to add potassium carbonate, wherein the mass ratio of quaternized phenol, 4,4-dichlorodiphenyl sulfone, bisphenol A, and potassium carbonate is 1.5:1:1.5:0.2, first raising the temperature to 170° C. for azeotropic dehydration for 4 hours, then raising the temperature to 180° C. for reaction for 10 hours, cooling, centrifuging, washing with water and ethanol in sequence, and drying to obtain quaternized polysulfone;
[0035] (5) Add quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid into a stirrer, wherein the mass ratio of quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid is 2.5:1:2.6:1.8, and stir for 4 hours to obtain a new salt-resistant polymer oil displacement agent.
[0036] Example 3
[0037] (1) 40 parts by weight of coal tar pitch was crushed and passed through a 190-mesh sieve to obtain 30 parts by weight of powder, which was then dried at 70° C. to constant weight, and then a mixed solution of 12.5 parts by weight of potassium hydroxide and 25 parts by weight of deionized water was added thereto, and 3.5 MPa of oxygen was introduced. After 1 hour, the temperature was raised to 135° C. and oxidized at a constant temperature for 2.5 hours. After the oxidation was completed, the powder was filtered to obtain alkalized coal tar pitch;
[0038] (2) adding alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol to deionized water to obtain solution A, wherein the mass ratio of alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol is 1.35:1:2.2:2.3:1.1, stirring, adding a mixed solution B of sodium persulfate solution and N,N'-methylenebisacrylamide solution, wherein the mass ratio of sodium persulfate solution and N,N'-methylenebisacrylamide solution is 1.0:1.2, and the mass ratio of solution A to mixed solution B is 1.35:1, stirring evenly, reacting in a water bath at 80°C for 15 minutes, filtering and drying to obtain coal tar resin;
[0039] (3) adding 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent to dissolve it, and then adding p-hydroxyphenylethanol to react, wherein the mass ratio of 2,3-epoxypropyltrimethylammonium chloride to p-hydroxyphenylethanol is 1.2:1, heating in a water bath at 80° C., reacting for 8 hours, washing with anhydrous ethanol after the reaction, and drying to obtain quaternized phenol;
[0040] (4) adding quaternized phenol, 4,4-dichlorodiphenyl sulfone, and bisphenol A to N-methylpyrrolidone, stirring evenly, and then continuing to add potassium carbonate, wherein the mass ratio of quaternized phenol, 4,4-dichlorodiphenyl sulfone, bisphenol A, and potassium carbonate is 1.35:1:1.2:0.15, first raising the temperature to 160° C. for azeotropic dehydration for 3 hours, then raising the temperature to 140° C. for reaction for 8 hours, cooling, centrifuging, washing with water and ethanol in sequence, and drying to obtain quaternized polysulfone;
[0041] (5) Add quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid into a stirrer, wherein the mass ratio of quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid is 2.3:1:2.45:1.65, and stir for 3 hours to obtain a new salt-resistant polymer oil displacement agent.
[0042] Example 4
[0043] (1) 30 parts by weight of coal tar pitch were crushed, passed through a 180-mesh sieve, and 20 parts by weight of powder were obtained, which was then dried at 60° C. to constant weight, and then a mixed solution of 10 parts by weight of potassium hydroxide and 20 parts by weight of deionized water was added thereto, and 3 MPa of oxygen was introduced. After 1 hour, the temperature was raised to 220° C. and oxidized at a constant temperature for 2 hours. After the oxidation was completed, the powder was filtered to obtain alkalized coal tar pitch;
[0044] (2) adding alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol to deionized water to obtain solution A, wherein the mass ratio of alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol is 1.2:1:2.1:2.2:0.8, stirring, adding a mixed solution B of sodium persulfate solution and N,N'-methylenebisacrylamide solution, wherein the mass ratio of sodium persulfate solution and N,N'-methylenebisacrylamide solution is 0.8:1.1, and the mass ratio of solution A to mixed solution B is 1.2:1, stirring evenly, reacting in a water bath at 70°C for 10 minutes, filtering and drying to obtain coal tar resin;
[0045] (3) adding 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent to dissolve it, and then adding p-hydroxyphenylethanol to react, wherein the mass ratio of 2,3-epoxypropyltrimethylammonium chloride to p-hydroxyphenylethanol is 1.3:1, heating in a water bath at 90° C., reacting for 10 hours, washing with anhydrous ethanol after the reaction, and drying to obtain quaternized phenol;
[0046] (4) adding quaternized phenol, 4,4-dichlorodiphenyl sulfone, and bisphenol A to N-methylpyrrolidone, stirring evenly, and then continuing to add potassium carbonate, wherein the mass ratio of quaternized phenol, 4,4-dichlorodiphenyl sulfone, bisphenol A, and potassium carbonate is 1.5:1:1.5:0.2, first raising the temperature to 170° C. for azeotropic dehydration for 4 hours, then raising the temperature to 180° C. for reaction for 10 hours, cooling, centrifuging, washing with water and ethanol in sequence, and drying to obtain quaternized polysulfone;
[0047] (5) Add quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid into a stirrer, wherein the mass ratio of quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid is 2.3:1:2.45:1.65, and stir for 3 hours to obtain a new salt-resistant polymer oil displacement agent.
[0048] Example 5
[0049] (1) 50 parts by weight of coal tar pitch was crushed and passed through a 200-mesh sieve to obtain 40 parts by weight of powder, which was then dried at 80° C. to constant weight, and then a mixed solution of 15 parts by weight of potassium hydroxide and 30 parts by weight of deionized water was added thereto, and 4 MPa of oxygen was introduced. After 1 hour, the temperature was raised to 250° C. and oxidized at a constant temperature for 3 hours. After the oxidation was completed, the powder was filtered to obtain alkalized coal tar pitch;
[0050] (2) adding alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol to deionized water to obtain solution A, wherein the mass ratio of alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone, and polyethylene glycol is 1.5:1:2.3:2.4:1.4, stirring, adding a mixed solution B of sodium persulfate solution and N,N'-methylenebisacrylamide solution, wherein the mass ratio of sodium persulfate solution and N,N'-methylenebisacrylamide solution is 1.2:1.3, and the mass ratio of solution A to mixed solution B is 1.5:1, stirring evenly, reacting in a water bath at 90°C for 20 minutes, filtering and drying to obtain coal tar resin;
[0051] (3) adding 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent to dissolve it, and then adding p-hydroxyphenylethanol to react, wherein the mass ratio of 2,3-epoxypropyltrimethylammonium chloride to p-hydroxyphenylethanol is 1.2:1, heating in a water bath at 80° C., reacting for 8 hours, washing with anhydrous ethanol after the reaction, and drying to obtain quaternized phenol;
[0052] (4) adding quaternized phenol, 4,4-dichlorodiphenyl sulfone, and bisphenol A to N-methylpyrrolidone, stirring evenly, and then continuing to add potassium carbonate, wherein the mass ratio of quaternized phenol, 4,4-dichlorodiphenyl sulfone, bisphenol A, and potassium carbonate is 1.35:1:1.2:0.15, first raising the temperature to 160° C. for azeotropic dehydration for 3 hours, then raising the temperature to 140° C. for reaction for 8 hours, cooling, centrifuging, washing with water and ethanol in sequence, and drying to obtain quaternized polysulfone;
[0053] (5) Add quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid into a stirrer, wherein the mass ratio of quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid is 2.1:1:2.3:1.5, and stir for 2 hours to obtain a new salt-resistant polymer oil displacement agent.
[0054] Comparative Example 1
[0055] Add epoxy nano-silica and 2-acrylamide-2-methylpropane sulfonic acid into a stirrer, wherein the mass ratio of epoxy nano-silica to 2-acrylamide-2-methylpropane sulfonic acid is 1:1.5, and stir for 2 hours to obtain a new salt-resistant polymer oil-displacing agent.
[0056] NaCl was used to simulate groundwater conditions. The NaCl concentration was 80 / g / L. The oil displacement agent salt resistance test was carried out. The viscosity of the oil displacement agent solution was 0.6%. The test results are shown in Table 1.
[0057] Table 1: Salt resistance test of oil displacement agents.
[0058]
[0059]
[0060] It can be seen from Table 1 that the novel salt-resistant polymer oil-displacing agent of the present invention has a good salt-resistant effect.
[0061] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a novel salt-resistant polymer oil-displacing agent, characterized in that: The preparation method of the novel salt-resistant polymer oil-displacing agent comprises the following steps: (1) 30-50 parts by weight of coal tar pitch is crushed, passed through a 180-200 mesh sieve, and 20-40 parts by weight of powder is obtained, which is then dried at 60-80°C to constant weight, and then a mixed solution of 10-15 parts by weight of potassium hydroxide and 20-30 parts by weight of deionized water is added, and 3-4 MPa of oxygen is introduced. After 1 hour, the temperature is raised to 220-250°C, and the oxidation is carried out at a constant temperature for 2-3 hours. After the oxidation is completed, the powder is filtered to obtain alkalized coal tar pitch; (2) adding alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone and polyethylene glycol to deionized water to obtain solution A, adding a mixed solution B of sodium persulfate solution and N,N'-methylenebisacrylamide solution after stirring, stirring evenly, reacting in a water bath at 70-90°C for 10-20 minutes, filtering and drying to obtain coal tar resin; (3) Add quaternized phenol, 4,4-dichlorodiphenyl sulfone and bisphenol A to N-methylpyrrolidone, stir evenly, then continue to add potassium carbonate, first raise the temperature to 150-170°C for azeotropic dehydration for 2-4 hours, then raise the temperature to 100-180°C for reaction for 6-10 hours, cool, centrifuge, wash with water and ethanol in turn, and dry to obtain quaternized polysulfone; (4) Adding quaternary ammonium polysulfone, epoxy nano-silica, coal tar resin, and 2-acrylamide-2-methylpropane sulfonic acid into a stirrer and stirring for 2-4 hours to obtain a new salt-resistant polymer oil displacement agent; The preparation method of the quaternized phenol in (3) is as follows: 2,3-epoxypropyltrimethylammonium chloride is added to N,N-dimethylformamide solvent to dissolve it, and then p-hydroxyphenylethanol is added to react, and heated in a water bath at 70-90° C. for 6-10 hours. After the reaction is completed, the quaternized phenol is washed with anhydrous ethanol and dried to obtain the quaternized phenol; The mass ratio of the 2,3-epoxypropyltrimethylammonium chloride to p-hydroxyphenylethanol is 1.1-1.3:
1.
2. The method for preparing the novel salt-resistant polymer oil-displacing agent according to claim 1, characterized in that: The mass ratio of alkalized coal tar, acrylic acid, acrylamide, phenyl vinyl sulfone and polyethylene glycol in the solution (2) A is 1.2-1.5:1:2.1-2.3:2.2-2.4:0.8-1.
4.
3. The method for preparing the novel salt-resistant polymer oil-displacing agent according to claim 1, characterized in that: The mass ratio of the sodium persulfate solution to the N,N'-methylenebisacrylamide solution in the mixed solution (2) B is 0.8-1.2:1.1-1.
3.
4. The method for preparing the novel salt-resistant polymer oil-displacing agent according to claim 1, characterized in that: The mass ratio of solution A to mixed solution B in (2) is 1.2-1.5:
1.
5. The method for preparing the novel salt-resistant polymer oil-displacing agent according to claim 1, characterized in that: The mass ratio of quaternized phenol, 4,4-dichlorodiphenyl sulfone, bisphenol A and potassium carbonate in (3) is 1.2-1.5:1:0.9-1.5:0.1-0.
2.
6. The method for preparing the novel salt-resistant polymer oil-displacing agent according to claim 1, characterized in that: The mass ratio of quaternized polysulfone, epoxy nano-silica, coal tar resin and 2-acrylamide-2-methylpropane sulfonic acid in (4) is 2.1-2.5:1:2.3-2.6:1.5-1.
8.
7. A novel salt-resistant polymer oil-displacing agent, characterized in that: The preparation method is obtained by any one of claims 1 to 6.
Citation Information
Patent Citations
Modified epoxy asphalt particle, preparation method and applications thereof
CN110922772A
High-temperature-resistant base bionic wall-fixing agent for water-based drilling fluid as well as preparation method and application of high-temperature-resistant base bionic wall-fixing agent
CN115960304A